ANALYSIS OF TEST INSTRUMENTS BASED ON HOTS CRITICAL THINKING ON PHYSICS IN THE SENIOR HIGH SCHOOL - Sabani; Bunawan, Wawan; Ramadhani, Irham; Tri Agung, Maulana (International Journal of Research -GRANTHAALAYAH, 2022)
Although learning has been implemented online because of the ongoing Covid-19 Pandemic, it is hoped that it does not eliminate the essence of the implementation of the revised K-13 curriculum, namely the scientific approach to learning process. The implementation of the scientific approach will structure the mind set of students to criticize a problem in their everyday life. This is what is required in the implementation of the revised K-13 curriculum, where critical thinking is a high-level thinking ability that students must familiarize with. HOTS questions are a measurement instrument used to measure higher order thinking skills, namely thinking skills that do not just remember, restate, or refer without processing. The purpose of this study is to: 1) determine the HOTS-based test instrument for high school critical thinking that has been used in the learning process and learning evaluation. 2). Know the level of difficulty and difference in power of the instrument and the effectiveness of the answer keys for high school tests. This research is a descriptive research with qualitative and quantitative approaches to documentation study. The findings in the study indicate that the test instruments used at the high school level have not met the criteria for HOTS high-level thinking. As for the results of the calculation of the difficulty level of the test, 8% of the questions were in the easy category, 46% in the medium category and 46% in the difficult category. For the difference in power category, 42% of the questions were in the bad category, 33% were in the enough category, while 4% were in the good category and 21% of the questions were in the very good category. The limitation of this research is the HOTS category of critical thinking test instruments..